The similarity of Ali (as) and Jesus (PBUH) in Islamic tradition - Mahdi Hasanzadeh; Ali Ashraf-Imami; Sorush Ghanbari (Comparative Theology, 2015)
According to the teachings of the Shia, Imam Ali (AS) has unique features by which he earned the merits of becoming the successor to the Prophet (pbuh) as the Imam and Wali. One of the most important of his features is his similarity to the Jesus as one of the greatest prophets before Prophet Muhammad (pbuh). This similarity was first mentioned in some Islamic traditions, especially the ones narrated through Shiite Isnad in interpretation of the verses 57-59 of the Surta Az-Zukhruf. In these traditions, the Prophet has regarded the Position of Imam Ali (AS) in his nation the same as Jesus's Position among the Israel. The Quran has cited the inimical arguments of the Arab infidels against this prophet's saying: they considered the worshiping of their own gods better than accepting Prophet's remark in equating his cousin with Jesus (pbuh). By resorting to this remark, the infidels regarded worshiping their own gods more preferable than deifying a man. Therefore, the first and most prominent similarity between Imam Ali (AS) and Jesus Christ (pbuh) is attributing divinity to Imam Ali (AS), at least by some of his extreme lovers. The Quranic command saying: "Do not Exaggerate about your religion… .(Quran 4:17) refers to the Christian extremism in deifying Jesus, But soon word Ghali was borrowed from this verse and used to refer to Shiite extremists. Moreover, the Quran (4: 159), talks about the advent of Jesus Christ to his followers before their death .The same concept has been mentioned in Shiite traditions about Imam Ali (AS), according to which, he is believed to be present beside every dying Muslim individual. This appearance of Imam Ali (AS) would remind us the idea of Imam Ali's (AS) return to this world. Thus, the return of Imam Ali (AS) to this world is the third similarity between Imam Ali (AS) and Jesus Christ (PBUH). Not only the return of Jesus has been mentioned in in the Christian tradition as the one manifested to the apostles after his ascension and also his return as the Messiah, the savior of the world, but in the Islamic tradition and the Koran (AZ-ZUKHRUF: 61) it is also pointed out that Jesus's (pbuh ) return is certainly a sign for resurrection. It is so interesting that in Shiite commentaries under this verse and other Quranic verses (Naml:2) the return of Imam Ali (AS) to the world has been mentioned as eschatological signs. This return happens due to the high position of Jesus Christ and Ali (AS) both of whom in Christian and Shiite traditions possess the two concepts of ascending and descending. It is narrated from Imam Ali (AS) that he described himself as having the quality of return. The reflection of such remarks among the Shiite extremists led to the denial of Imam Ali's death and his divinity. The extremists who were known as Nasiris expressed the divinity of Imam Ali (AS) in the form of trinity and in Baktashi Sufism; this concept has been elaborated as the three hypostases of Allah, Muhammad and Ali. In Ibn Arabi mysticism the divinity has been manifested in ultimate authority he considers for both of them. Besides all these similarities, the miracles done by Imam Ali (like: the revival of the dead, speaking in the cradle, and rising in the clouds) are all similar to the ones narrated for Jesus Christ. Furthermore, Imam Ali's moral features like his chivalry and piety match the qualities of Jesus inferred from his biography.